2021
DOI: 10.1210/clinem/dgab089
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytosis in a Large Cohort of Trans Men Using Testosterone: A Long-Term Follow-Up Study on Prevalence, Determinants, and Exposure Years

Abstract: Context Erythrocytosis is a known side effect of testosterone therapy that can increase the risk of thromboembolic events. Objectives To study the prevalence and determinants in the development of erythrocytosis in trans men using testosterone. Design A twenty year follow-up study in adult trans men who started testosterone therapy, and had monitoring of hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 35 publications
0
27
0
1
Order By: Relevance
“…But in trans women treated with CPA, a negative effect is seen on HDL levels [91,93,94,98]. Trans men have an increased risk of elevated hematocrit levels, but this is manageable [61,94,101,102]. The discrepancy between the effects of GAHT on cardiovascular risk factors and the available data on cardiovascular endpoints remains to be elucidated against the backdrop of changing hormonal interventions over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But in trans women treated with CPA, a negative effect is seen on HDL levels [91,93,94,98]. Trans men have an increased risk of elevated hematocrit levels, but this is manageable [61,94,101,102]. The discrepancy between the effects of GAHT on cardiovascular risk factors and the available data on cardiovascular endpoints remains to be elucidated against the backdrop of changing hormonal interventions over time.…”
Section: Discussionmentioning
confidence: 99%
“…Trans men receiving shorter-acting testosterone esters had a greater increase ( 0.8%) in serum hematocrit levels compared to trans men receiving 3 monthly injections of testosterone undecanoate, which might be explained by pharmacokinetic profiles [101]. A long-term follow-up cohort study from Madsen et al [102] reported erythrocytosis in 11% (hematocrit >0.50 l/l), 3,7% (>0.52 l/l), and 0.5% (>0.54 l/l) of trans men (n = 1037, mean age at start of GAHT = 22.5) on testosterone therapy. The largest increase was seen in the first year of testosterone therapy, but the probability of developing erythrocytosis still increased in the following 20 years (10% after 1 year, 38% after 10 years) [102].…”
Section: Risk Factors For Trans Menmentioning
confidence: 99%
See 1 more Smart Citation
“…TC17 was also characterized by polycythemia. High levels of HCT and RBCs are typically increased in TGM, and the subsequent polycythemia is considered an adverse drug reaction lifelong hormonal therapy [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…For those individuals on progesterone, use of micronized progestin rather than medroxyprogesterone acetate has been shown to decrease the risk of thromboembolism, at least among postmenopausal cisgender women [ 71 ]. Among trans men, testosterone use has also been associated with an increased risk of erythrocytosis and the development of blood clots, particularly during the first year of GAHT [ 72 ]. For all individuals on GAHT, healthcare providers should carefully explain the risk of thromboembolic events and evaluate for the presence of other CVD risk factors, particularly smoking, to provide a holistic risk-reduction approach [ 73 ].…”
Section: Clinical Vignettementioning
confidence: 99%